2022
DOI: 10.3389/fphys.2021.810473
|View full text |Cite
|
Sign up to set email alerts
|

Serum and Glucocorticoid-Inducible Kinase 3/Nedd4-2 Signaling Pathway Participates in Podocyte Injury by Regulating the Stability of Nephrin

Abstract: Serum and glucocorticoid-inducible kinase 3 (SGK3) is involved in maintaining podocyte function by regulating the protein levels of podocin and CD2-associated protein. Nephrin is also one of the slit diaphragm proteins of podocytes, but whether SGK3 participates in podocyte injury by regulating the levels of nephrin remains unclear. In this study, we focused on whether SGK3 affects nephrin levels and the mechanisms involved in the same. In the kidneys of adriamycin (ADR)-induced podocyte injury mouse model, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…It has been reported that the inhibition of SGK1 can exacerbate the proinflammatory ability of microglia and negatively regulate TLR-induced inflammation (Zhou et al, 2015;Inoue et al, 2016). Additionally, our previous studies confirmed that SGK3 deletion could cause podocyte damage and increase proteinuria in mice (Dong et al, 2021). However, whether SGK3 is closely relevant to TECs and immune cells has not yet been explored.…”
Section: Introductionmentioning
confidence: 71%
“…It has been reported that the inhibition of SGK1 can exacerbate the proinflammatory ability of microglia and negatively regulate TLR-induced inflammation (Zhou et al, 2015;Inoue et al, 2016). Additionally, our previous studies confirmed that SGK3 deletion could cause podocyte damage and increase proteinuria in mice (Dong et al, 2021). However, whether SGK3 is closely relevant to TECs and immune cells has not yet been explored.…”
Section: Introductionmentioning
confidence: 71%
“…We previously reported that the SGK3/Nedd4-2 signaling pathway is involved in the pathogenesis of CKD by regulating the degradation of nephrin and ezrin through ubiquitin-proteasome-mediated protein degradation 32 . To explore how SGK3 specifically regulates the degradation of Pit-1.…”
Section: Resultsmentioning
confidence: 99%
“…CXCL1 is an NF-κB-dependent potent neutrophil chemoattractant that was found to be expressed in Actn4 KO podocytes and upregulated in FSGS kidney biopsies 35 . Among the most downregulated genes, the E3-ubiquitin ligase NEDD4 was recently found to be involved in ubiquitin-mediated proteasomal degradation of nephrin 36 . Therefore, this downregulation might represent an attempt to stabilize nephrin under stress.…”
Section: Discussionmentioning
confidence: 99%